A portable and reliable tool for on-site physical reaction time (RT) measurement - B. Harper; M. Shiraishi; R. Soangra (Invention Disclosure)
The drop-stick test system (DTS) invention has the capability to measure reaction accurately for sideline mild traumatic brain injury (mTBI) assessment. The reaction time (RT) measurements showed moderate to good inter-instrument reliability with an overall ICC of 0.82 (95 % CI 0.78–0.85). RT is a useful biomarker of mTBI or concussion, but existing technologies in controlled laboratory environments are not feasible for assessments in the field. With wearable technologies and wireless connection with smartphones, it is now easier to conduct RT assessments on the field. The purpose was to develop a portable DTS involving wearable inertial sensors translatable from the laboratory to the sideline assessments on athletic fields. This project investigated if RT measurements using sensors are reliable metrics when compared to the gold-standard motion capture laboratory-test. The intent was to invent and assess the reliability of a clinical DTS using sensors in conjunction with an easy RT measurement protocol. The integrated inertial sensors in the DTS have the potential to reliably capture RT, allowing it to more easily translate into the training room or field environment.